FENOMENA AL-LIWATH DALAM PARADIGMA (FILSAFAT PANCASILA) SILA KETUHANAN YANG MAHA ESA DAN KONSEP HUKUM ISLAM - Mesri Wahyuni; Zulkifli Zulkifli (Institut Agama Islam Negeri Batusangkar, 2023)
This study examines the phenomenon of al-liwath in the paradigm (Philosophy of Pancasila), the Precepts of the Almighty Godhead, and in Islamic Law. The problem is whether or not liwath contradicts the first pancasila, violates pancasila or not and aims to find out the legal position of al-liwath in terms of Islamic law. From these problems arises the question of how the Philosophical View of Pancasila, the First Precept on the al-liwath Phenomenon in Indonesia and how the Islamic Law View on the al-liwath Phenomenon. This research is library research. Data is obtained through secondary sources (data) with primary material. After the data is collected, it is processed by reviewing with the author's research. Next, the data is narrated descriptively. The results are discussed with the theories put forward. The study found that Pancasila serves as the highest source of law in Indonesia. Indonesia does not allow behavior that is contrary to the noble values of Pancasila, because the Unitary State of the Republic of Indonesia is a legitimate state based on Pancasila and the 1945 Constitution. All people of the Unitary State of the Republic of Indonesia have faith and devotion to God Almighty by adhering to moral and ethical values, noble morals, and noble national personality. In Islamic law, Allah Almighty forbids all unnatural actions because it has wisdom that is very beneficial for humans in thinking. Liwath or homosexual acts are forbidden by sharia and are more heinous than adultery. The punishment for homosexuality is dissenting among jurisprudence scholars, among others: Absolute Suicide, Sanction Equivalent to Zina and Subject to Ta' zir Law.